Comparing Pathways for Retinal and Neuronal Degeneration in Drosophila melanogaster - Thuery, Guillaume Charles (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2023)
Past work to understand the mechanisms of cellular degeneration has either focused on retinal degeneration or neurodegeneration. These studies have revealed that the integrated stress response (ISR) and RNA binding proteins (RBPs) contribute to pathogenesis, although the exact players and roles remain elusive. The overarching aim of this thesis was to understand the role of the ISR, of ribonucleoprotein (RNP) granule formation, and of novel RBPs in two different models for cellular degeneration using similar genetic tools, gaining additional insights on potential overlapping molecular pathways in Drosophila melanogaster. The first results chapter demonstrates that proteins involved in the ISR, in RNP granule formation, and in RNA regulation contribute to the degenerative phenotype observed in the retinas of rdgB mutants. The second results chapter confirms crucial, but contrasting, roles for the RNP granule components Ataxin-2 and Rasputin in the HttQ138 neurodegenerative model of Huntington's disease (HD). In addition, the results hint at the possibility that the ISR contributes to the development of neurodegeneration in HD. Overall, this work has demonstrated that modulating the ISR and RNP granule components can reduce the degenerative phenotype in models for both neurodegeneration and retinal degeneration. Future work should seek to clarify why the activity of the ISR and the RNP granule components worsens the phenotypes induced in these models of cellular degeneration.
APPROVED
Keywords: Neurodegeneration; Cellular degeneration; Integrated stress response; Retinal degeneration; Drosophila; RNA; ataxin-2